Design And Optimization Of Transition For Air-Filled Substrate Integrated Waveguide - Mansor, Nur Hidayah (2018)
Air-filled substrate integrated waveguide (SIW) is a new form of transmission lines that have been used as interconnect with conventional SIW circuits to reduce losses in the circuits. For an effective interconnection, various proposals for the transition between the air-filled and dielectric-filled media in SIW have been given. To increase the performance of the transition, the insertion and return losses along the transition must be minimized. However, the losses in the transition are not well understood. This is because the propagation of electromagnetic waves along the inhomogeneous media with varying geometry is difficult to characterize with respect to losses. This thesis presents an in-depth study to characterize the propagation of the waves and losses in the transition using full-wave analysis. From the assessment of the transition geometry from air-filled to dielectric-filled SIW, an optimization procedure is developed to further minimize the losses in the structure. Defining the shape of the transition taper with the cubic clamped spline function, the developed procedure shows that further reduction of losses is possible within the prescribed frequency bands, i.e., Ka-band (26-40 GHz) and U-band (40-60 GHz). Furthermore, the length of the transition taper can also be significantly reduced while maintaining an optimal quality of signal transmission in the transition. Hence, by optimizing the transition geometry, the signal in the form of electromagnetic waves will pass through the transition with minimal return loss and insertion loss. The numerical studies in specific cases of the transition optimization show an improvement of 45% return loss at Ka-band frequencies and 48.3% return loss at U-band frequencies. Meanwhile, the improvements of transmission loss by 3.1% at Ka-band and 4.0% at U-band were obtained. The findings of the present study will contribute to the development of a more compact design of coplanar circuits for any frequency bands with better performance.